The impact of information technology maturity on firm performance considering the moderating role of relational maturity: an empirical research. (2016) - Keramati, Abbas; Afshari-Mofrad, Masoud; Behmanesh, Iman; Gholami, Reihaneh
The role of information technology (IT) in firm performance remained an open research question. This research provides new discernments for better understanding the mechanisms supporting this relationship by analysing the effects of IT maturity, complementary investments, process orientation and relational maturity on firm performance. We expanded existing literature by developing and empirically testing a model where: 1) the performance is affected by IT maturity; 2) relational maturity can reinforce this relationship. The correctness of the suggested model was statistically approved by gathering data from Iran electric industry and using MPLUS3 software. This research proves that there is a positive significant correlation between IT maturity and performance. Also, we find that IT maturity affects firm performance by enabling organisational processes. Based on the findings of this research investigation, relational maturity of the organisation plays a moderating role in the relationship between IT maturity and firm performance. Findings of this research will be of epical interest to both academics and practitioners of information systems.